A New Speed Multiplier Coaxial Magnetic Gear - Mohd Ab Halim, Mohd Firdaus; Raja Othman, Raja Nor Firdaus Kashfi; Ab Rahman, Azhan; Sulaiman, Erwan (EMW Publishing, 2020)
Due to certain conditions, electrical motor (EM) that operates at high speed may lead to magnetic saturation, thermal issue, and stress to rotor structure. Magnetic gear (MG) designed for speed multiplier enables the prime mover from EM to operate at lower speed while the output gear multiplies the speed by its designated gear ratio at reduced torque. In this paper, a new coaxial magnetic gear is designed for speed multiplier. The role between inner yoke with PM and pole piece is switched. The inner part of magnetic gear is made to be stationary while the pole piece becomes inner rotor. The working principle is presented analytically based on flux modulation techniques for torque and speed transmission. Torque characteristic and gear efficiency are analysed using finite element and compared with existing speed multiplier magnetic gear with the same gear ratio of 7/3. Based on the simulation result, the proposed speed multiplier MG offers 16% better torque density and 12% higher gear efficiency at higher speed range. The structure of the inner rotor is also found to be more robust as only pole piece ring together with plastic holding frame is rotated instead of yoke with PM